Tick-borne viruses in Europe - Hubálek, Zdenek; Rudolf, Ivo (Parasitology research, 2012)
The aim of this review is to present briefly background information on 27 tick-borne viruses ("tiboviruses") that have been detected in Europe, viz flaviviruses tick-borne encephalitis (TBEV), louping-ill (LIV), Tyuleniy (TYUV), and Meaban (MEAV); orthobunyaviruses Bahig (BAHV) and Matruh (MTRV); phleboviruses Grand Arbaud (GAV), Ponteves (PTVV), Uukuniemi (UUKV), Zaliv Terpeniya (ZTV), and St. Abb's Head (SAHV); nairoviruses Soldado (SOLV), Puffin Island (PIV), Avalon (AVAV), Clo Mor (CMV), Crimean-Congo hemorrhagic fever (CCHFV); bunyavirus Bhanja (BHAV); coltivirus Eyach (EYAV); orbiviruses Tribec (TRBV), Okhotskiy (OKHV), Cape Wrath (CWV), Mykines (MYKV), Tindholmur (TDMV), and Bauline (BAUV); two thogotoviruses (Thogoto THOV, Dhori DHOV); and one asfivirus (African swine fever virus ASFV). Emphasis is laid on the taxonomic status of these viruses, range of their ixodid or argasid vectors and vertebrate hosts, pathogenicity for vertebrates including humans, and relevance to public health. In general, three groups of tibovirus diseases can be recognized according to main clinical symptoms produced: (i) febrile illness-usually with a rapid onset, fever, sweating, headache, nausea, weakness, myalgia, arthralgia, sometimes polyarthritis and rash; (ii) the CNS affection-meningitis, meningoencephalitis or encephalomyelitis with pareses, paralysis and other sequelae; (iii) hemorrhagic disease. Several "European" tiboviruses cause very serious human (TBEV, CCHFV) or animal (LIV, ASFV) diseases. Other arboviruses play definite role in human or animal pathology though the disease is usually either less serious or infrequently reported (TYUV, BHAV, AVAV, EYAV, TRBV, DHOV, THOV). The other European arboviruses are "orphans" without a proven medical or veterinary significance (BAHV, MTRV, MEAV, GAV, PTVV, ZTV, SAHV, UUKV, SOLV, PIV, AVAV, CMV, OKHV, CWV, MYKV, TDMV, BAUV). However, certain arbovirus diseases of free-living vertebrates (but also those of domestic animals and even man) may often pass unnoticed or misdiagnosed and eventually, they might potentially appear as emerging diseases. Active search for new tiboviruses or for new, pathogenic variants of the known tiboviruses in Europe should therefore continue.
Keywords: virové nemoci; Animals; Disease Vectors; Virus Diseases; Viruses; infekce přenášené vektorem; viry; lidé; klíšťata; Europe; zvířata; Evropa; Tick-Borne Diseases; Ticks; nemoci přenášené klíšťaty; Humans